The effect of parasitism on nutrient metabolism and productivity in small ruminants. - Akinbamijo, O.O. (Wageningen University & Research, 1994)
The investigation of voluntary feed intake (VFI) and nitrogen retention (NRET) during parasitic infections in small ruminants is the central theme of this thesis. An attempt was made to examine the effects of trypanosomiasis on feed intake, digestibility, nitrogen retention and animal products. In addition, a similar investigation was conducted during a low to medium level fascioliasis infection in Menz sheep. The relationship between digestible organic matter intake (DOMI) rectal temperature (RT) and maintenance requirements was also studied in healthy goats.